Primary Meningococcal Polyarthritis in an Adult Woman - José Celso Giordan Cavalcanti Sarinho; Marília Soares e Silva Arcadipane; Graziela Tavares Miola Menezes; Danilo Fernando Costa Duarte; Waldenise Cossermelli; Ivan Aprahamian (Case Reports in Medicine)
Primary joint infection caused by the Gram-negative bacteria Neisseria meningitidis is rare. Normally, joint involvement comes secondary to meningitis or severe sepsis caused by this agent. When primary arthritis is seen, monoarthritis is the most common presentation. A meningococcal polyarthritis is described in less than 10 case reports according to current literature. This case report aims to briefly review this rare clinical event in an adult woman with no previous history of rheumatological disease. Early diagnosis of polyarthritis caused by meningococcal bacteria usually present a good prognosis when properly treated.